Drug Information and Counselling Services in Self-Medication at Apotek X Sleman - Laka, Lusiana Cindy Putri; Soegiantoro, Didiek Hardiyanto; Atmaja, Sarah Puspita (Jurnal EduHealth, 2025)
Self-medication is a common practice for people to treat minor complaints without a doctor's prescription. However, without adequate drug information and counselling, self-medication can pose a risk of inappropriate drug use. This study aims to evaluate the drug information and counselling services provided to self-medication patients at the Apotek X, Sleman, with a focus on patient willingness to receive counselling, patient profile, counselling materials, and duration of counselling. This study used a descriptive observational method with a quantitative approach, conducted during February 2025. The sample consisted of 343 patients who met the inclusion criteria, with data collected through direct observation sheets of interactions between pharmacists and patients. The results showed that 61.52% of patients were willing to receive counselling services, while 38.48% refused. The patient profile was dominated by paediatrics (52.77%) and geriatrics (39.36%). The most frequently delivered counselling material was drug efficacy (56.85%), followed by how to use (37.61%) and dosage (25.07%). Other important information such as side effects, storage, and actions when forgetting to take medication were hardly provided. The duration of counselling mostly lasted less than five minutes (56.27%), indicating limited time in delivering information. The conclusion of this study is that although most patients are willing to receive counselling, the quality and scope of information provided still needs to be improved, especially in terms of drug safety. There is a need for improvements in counselling protocols and pharmacist training to improve the quality of self-medication services in community pharmacies.